The History of Dictatorship: Custom, Authority, and Power in Precolonial and Colonial Uganda - Yahya Sseremba (Africa Spectrum, 2023)
Intervening in the enduring debate on the origins of the African state, this article examines the processes of producing custom in the Ugandan societies of precolonial Bunyoro and colonial Toro to trace the development of despotism. The participatory nature of generating customary truth in Bunyoro before European domination reflects the diffusion of power in a manner that hindered absolute rule. On the contrary, in colonial Toro, the inclusive mechanisms for making custom gave way to customary law produced by the colonial government and its native chiefs. This monopoly to determine customary law disguised as custom constituted the heart of the despotism of Toro Native Authority. Derivatively, the Rwenzururu resistance against Toro domination equally assumed a despotic character because it organised itself along the logic of the authority it confronted. The study interrogates the resurgent literature that associates the contemporary African state with precolonial history.